Partial Substitution of K by Na Alleviates Drought Stress and Increases Water Use Efficiency in Eucalyptus Species Seedlings - Mateus, Nikolas de Souza; Florentino, Antônio Leite; Santos, Elcio Ferreira; Ferraz, Alexandre de Vicente; Goncalves, José Leonardo de Moraes; Lavres, José (Frontiers in Plant Science, 2021)
Eucalyptus, the most widely planted tree genus worldwide, is frequently cultivated in soils with low water and nutrient availability. Sodium (Na) can substitute some physiological functions of potassium (K), directly influencing plants’ water status. However, the extent to which K can be replaced by Na in drought conditions remains poorly understood. A greenhouse experiment was conducted with three Eucalyptus genotypes under two water conditions (well-watered and water-stressed) and five combination rates of K and Na, representing substitutions of 0/100, 25/75, 50/50, 75/25, and 100/0 (percentage of Na/percentage of K), to investigate growth and photosynthesis-related parameters. This study focused on the positive effects of Na supply since, depending on the levels applied, the Na supply may induce plants to salinity stress (>100 mM of NaCl). Plants supplied with low to intermediate K replacement by Na reduced the critical level of K without showing symptoms of K deficiency and provided higher total dry matter (TDM) than those Eucalyptus seedlings supplied only with K in both water conditions. Those plants supplied with low to intermediate K replacement by Na had improved CO2 assimilation (A), stomatal density (Std), K use efficiency (UEK), and water use efficiency (WUE), in addition to reduced leaf water potential (Ψw) and maintenance of leaf turgidity, with the stomata partially closed, indicated by the higher values of leaf carbon isotope composition (δ13C‰). Meanwhile, combination rates higher than 50% of K replacement by Na led to K-deficient plants, characterized by the lower values of TDM, δ13C‰, WUE, and leaf K concentration and higher leaf Na concentration. There was positive evidence of partial replacement of K by Na in Eucalyptus seedlings; meanwhile, the ideal percentage of substitution increased according to the drought tolerance of the species (Eucalyptus saligna < Eucalyptus urophylla < Eucalyptus camaldulensis).